Estudio comparativo de la resistencia a la compresión del concreto usando tres marcas de cemento Portland tipo MS - Lucho Mendocilla, Loyda Elizabeth (2019)
Cement is a binder, the main material and indispensable for the construction of everything, so in the market this product is becoming increasingly broad and extensive brands that offer a variety of cements, for this reason is that many people find a task a bit difficult and overwhelming to decide for a type and proceed to purchase. The purpose of this research project is the comparative study of the compressive strength of concrete using three brands of portland type MS cement, which were Pacasmayo, Inka and Mochica for a resistance of 210 kg / cm2 at ages 7, 14, 21 and 28 days. For this, the characteristics of the aggregates were determined: Specific weight, volumetric weight compacted loose volumetric weight, percentage of absorption, humidity percentage and fineness modulus, which were made for the design of mixtures. The SLUMP test was performed with a settlement of 3 "to 4", 10 x 20 cm concrete specimens were prepared with three repetitions for each cement brand, cured for 7 days and finally the test pieces were broken according to the NTP 339.033CY ASTM C31. As a result of the average compressive strength at 28 days with Pacasmayo cement, we have 231.33 kg / cm2, Inka 238.33 kg / cm2 and Mochica 259 kg / cm2. It is concluded according to the results with Mochica cement, better concrete compression resistance was obtained after 28 days.